FEDERAL CHARACTER PRINCIPLE AND PRODUCTIVITY IN THE NIGERIAN PUBLIC SECTOR - Nandes Dickson, Cinjel; Salifu, David; Julius John, Achanya (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
Federal character principle is a doctrine which was introduced by the Nigerian government to ensure equitable representation and as well prevent the dominance of persons from a few states, religion or a particular ethnic group in the governance of the country and the sphere of the public sector. The principle was formally introduced in the 1979 constitution. The essence of the principle in itself is somewhat justifiable but the weakness in its application and its insensitivity to rationality; organizational norms and conventional pathway have marred and slowed down productivity in the public sector. The paper attempted to appraise the federal character principle and the challenges of productivity in the public services. The research design adopted in this study is thoroughly qualitative and the approaches combined with the design are chiefly analytical, descriptive and prescriptive by orientation. In interpreting our data, the relationship between the federal character principle and the productivity in the public service was established at both theoretical and empirical level. This was complemented by descriptive analysis. In doing this, information gathered were summarized and processed through critical qualitative analysis and the review of other empirical works appertains to the study. It was established that there is a strong connection between the federal character principle and dwindling of productivity in the public service. The study found that the federal character principle negate some organizational practice such as the use of merit, seniority and many more. Recommendations such as: an overhaul in the application of the doctrine, the need to build and redefine the principle within the conduit of rationality, the need for good governance and the respect for the norms of the public service, the need to re-modify the system to tandem with current realities and tools of organizational efficiency and effectiveness, and a lot of others were proffered.